A case of fulminant Clostridium perfringens infection: Role of macroscopic examination of the serum and peripheral blood smears. (2021) - Fukui, Sayato; Kogawa, Rikitake; Hojo, Atsuko; Kawamura, Wataru; Kura, Yoshimasa; Monma, Chie; Uehara, Yuki; Sawada, Umihiko
Abstract: A 69-year-old man was brought to our hospital by ambulance with a fever. The translucent pink color of the serum sample suggested severe hemolysis. His blood pressure dropped rapidly, and he later suffered a cardiopulmonary arrest and died approximately 30 h after arriving at our hospital. The day after the patient's death, Clostridium perfringens was detected in the blood culture taken at the time of hospital admission. When serum sample shows translucent pink to red color and bacilli from bacteria is identified in peripheral blood smear, Clostridium perfringens should be considered and appropriate medical treatment should be initiated immediately.